Influencing the Indians entrepreneur business success / Siti Farah Edwin - Edwin, Siti Farah (2014)
Since the beginning of its history, Malaysia has been a meeting place for a diverse range of external cultures and religions. As a result of these external influences, a new unified but distinguished Malay culture has emerged. Contemporary Malaysia represents a unique fusion of Malay, Chinese, and Indian traditions, creating a pluralistic and multicultural nation that has its character strongly rooted in social harmony, religion and pride in its ancestral background. With such a rich cultural heritage, acquiring the relevant skills and cultural knowledge in order to conduct business in Malaysia is crucial to your success. Sarawak is the largest of the 14 states of multilingual Malaysia, and is located on the island of Borneo. Sarawak has a population of 2,399,839 people consisting of 26 different ethnic groups. The largest group is the Iban with a population of 693,358, and this is followed by the Chinese 560,150, Malays 551,567, Bidayuh 192,960, Melanau 119,897, other Bumiputeras (sons of the soil) 152,074, Indians 7,188 and others which comprise of 113,772 non Malaysian citizens (Mukim, 2010) Kuching is the capital of Sarawak and is located in the Kuching Division, which is also known as the First Division. Kuching has a population of 598,617 (Mukim, 2010). The major religions in Sarawak are Christianity, Islam, Buddhism, and Taoism. Hinduism and Sikhism are practiced mostly by the Indians and Punjabis. In Sarawak, just as in other states in Malaysia, Malays are Muslims (David, 2003). People of Indian descent comprise about 7% of the population. South Indian Tamil have been coming to Malaysia since the 11th century. Inflow of Indian migrants began during the establishment of the Straits Settlements. They were brought in as labourers, traders, policeman, and construction workers. Large-scale migration took place in the early 1900s to work in the rubber plantations. The Tamils are concentrated on the West Coast of peninsular Malaysia. The Indian community is made up mostly of Tamils, but also includes Bangalis, Malayalis, Punjabis, Telugus, Gujaratis, and Sindhis. The main religion are Hinduism and Sikhism (Bhasin, 2010).